Awareness on risk factors of cardiovascular disorders – A survey - C, Pratheebha; V., Vishnu Priya; R. , Gayathri (International Journal of Psychosocial Rehabilitation, 2020)
Cardiovascular diseases (CVD) are conditions that affect the structures or functions of the heart, such as abnormal heart rhythms or arrhythmias, aorta disease, Marfan syndrome, congenital heart disease, or it can be coronary artery disease as well. Adequate awareness of CVD and their risk factors and understanding the consequences of cardiovascular disease is of great importance for CVD prevention and control. Questions were prepared and administered to 120 participants through the survey link. The study population were college students of the age group between 17 and 22 years. 74.5% of the survey population were aware of the risk factors associated with cardiovascular disorders. 88.8% of the participants agreed that smoking may make them more likely to develop heart disease. 83.8% of them agreed that maintaining blood pressure under control may reduce the chance of developing CVD. From the above survey conducted, 81.1% of the college students were aware of the risk factors and symptoms associated with CVD. Even among them, 56.2% of the survey participants know the preventable measures to be taken before developing CVD. More awareness may be created on lifestyle modifications among college students to prevent CVD.